2007
DOI: 10.1002/clc.20109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preload and Heart Rate on the Doppler and Tissue Doppler‐derived Myocardial Performance Index

Abstract: SummaryDoppler-derived myocardial performance index (MPI) has been described as a noninvasive measurement of LV function. Our aim was to investigate the effect of hemodialysis related volume reduction and heart rate changes on the Doppler-derived LV MPI, and Doppler tissue imaging (DTI) derived left and right ventricular MPI.Method: The study group comprised 32 consecutive patients (mean age: 43 ± 18 yrs) undergoing hemodialysis. Patients underwent echocardiography before and immediately after hemodialysis ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 24 publications
7
22
1
3
Order By: Relevance
“…Ozdemir et al found that increased Doppler-derived MPI was related to mortality in a variety of cardiac diseases [37]. And also his study had shown that while Doppler-derived MPI was affected by preload and heart rate, TDEderived MPI was not affected by either [37]. In this study, left ventricular MPI was significantly higher in CAE patients than the control group.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Ozdemir et al found that increased Doppler-derived MPI was related to mortality in a variety of cardiac diseases [37]. And also his study had shown that while Doppler-derived MPI was affected by preload and heart rate, TDEderived MPI was not affected by either [37]. In this study, left ventricular MPI was significantly higher in CAE patients than the control group.…”
Section: Discussionsupporting
confidence: 57%
“…Also, MPI is related to left ventricular dysfunction and clinical severity of heart failure and is a powerful parameter for the prognostic assessment of these patients [36]. Ozdemir et al found that increased Doppler-derived MPI was related to mortality in a variety of cardiac diseases [37]. And also his study had shown that while Doppler-derived MPI was affected by preload and heart rate, TDEderived MPI was not affected by either [37].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the MPI obtained by TDI can reduce inaccuracy due to heart-rate fluctuation [12,26]. A recently published study, Ozdemir et al [27], investigated the effect of hemodialysis-related volume reduction and heart-rate changes on the LV MPI using conventional PWD and MPI using TDI in adult ESRD patients. They showed that conventional PWD-derived MPI was influenced by preload and heart-rate changes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that increased Doppler-derived MPI is related to mortality in a variety of cardiac diseases [28]. Ozdemir et al [28] have shown in their study that while Doppler-derived MPI is affected by preload and heart rate, TDE-derived MPI is not affected by either. In our study, left ventricular lateral wall, interventricular septum and mean MPI was significantly higher in CAE patients than the control group.…”
Section: Discussionmentioning
confidence: 89%
“…Also, MPI is related to left ventricular dysfunction and clinical severity of heart failure and is a powerful parameter for the prognostic assessment of these patients [27]. It has been previously shown that increased Doppler-derived MPI is related to mortality in a variety of cardiac diseases [28]. Ozdemir et al [28] have shown in their study that while Doppler-derived MPI is affected by preload and heart rate, TDE-derived MPI is not affected by either.…”
Section: Discussionmentioning
confidence: 99%